Effects of Liquitein on weanling pigs administered a Porcine Circovirus Type 2 and Mycoplasma hyopneumoniae vaccine strategy - Myers, A.J.; Bergstrom, J.R.; Ratliff, B.W.; McKilligan, D.M.; Tokach, Michael D.; Goodband, Robert D.; DeRouchey, Joel M.; Nelssen, Jim L.; Dritz, Steven S. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2012)
A total of 180 nursery pigs (PIC 327 × 1050, initially 12.6 ± 0.22 lb, and 19 ± 2 d of age) were used in a 35-d study to determine the effects of Liquitein and a porcine circo- virus 2 (PCV2)/Mycoplasma hyopneumoniae (M. hyo) vaccine regimen on the growth performance of weanling pigs. Liquitein (TechMix, LLC Stewart, MN) is a watersoluble source of plasma and energy provided in the drinking water immediately after weaning. Pigs were randomly allotted to 1 of 4 treatments arranged in a 2 × 2 factorial with main effects of Liquitein (with or without) and PCV2/M. hyo vaccine regimen (vaccinates or non-vaccinates) with 5 pigs per pen and 9 pens per treatment. At wean- ing, pigs in the vaccinate group were given a full dose (2 mL) of ResprisureOne (Pfizer Animal Health, New York, NY) and Circumvent (Intervet/Schering-Plough Animal Health, Millsboro, DE). On d 21, pigs in the vaccinate group were administered a second full dose (2 mL) of Circumvent per label instructions. Liquitein was adminis- tered to the pigs via water medicators for the first 5 d after arrival to the nursery. No vaccine × Liquitein interactions occurred for ADG or F/G throughout the study. From d 0 to 5, non-vaccinated pigs had a tendency (P < 0.07) for increased ADG. From d 21 to 35, pigs previously administered Liquitein had greater ADFI (P = 0.05) than those not provided Liquitein; however, overall (d 0 to 35) Liquitein had no effects on growth performance. From d 0 to 35, vaccinated pigs had decreased (P < 0.01) ADG and ADFI compared with non-vaccinated pigs. In conclusion, administering Liquitein during the first 5 d in the nursery increased feed intake later in the nursery stage (d 21 to 35), but the response was not great enough to influence overall growth performance. Pigs administered the PCV2 and M. hyo vaccine regimen had decreased ADG and ADFI.
Keywords: Swine; Growth; Liquid supplement; PCV2; Weanling pig